2013
DOI: 10.1104/pp.113.222893
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Physiological Analysis of Al3+ and H+ Rhizotoxicities at Moderately Acidic Conditions    

Abstract: Al3+ and H + toxicities predicted to occur at moderately acidic conditions (pH [water] = 5-5.5) in low-Ca soils were characterized by the combined approaches of computational modeling of electrostatic interactions of ions at the root plasma membrane (PM) surface and molecular/physiological analyses in Arabidopsis (Arabidopsis thaliana). Root growth inhibition in known hypersensitive mutants was correlated with computed {Al 3+ } at the PM surface ({Al 3+ } PM ); inhibition was alleviated by increased Ca, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…A transcriptomic study of seedlings grown in an acidic environment showed that the stop1 mutant is defective for the expression of several genes, including genes involved in cell wall composition or modeling (Sawaki et al ., ). Furthermore, physiological studies suggested that stop1 seedlings are defective in a mechanism alleviating H + toxicity, perhaps via Ca 2+ stabilization of the cell wall (Kobayashi et al ., ). It is therefore tempting to speculate that even during WT embryogenesis STOP1 is participating in the making of root cells with a cell wall able to tolerate H + a few days after germination, and in stop1 seeds the root cell walls are somehow altered, leading to reduced root growth under acidic conditions.…”
Section: Discussionmentioning
confidence: 97%
“…A transcriptomic study of seedlings grown in an acidic environment showed that the stop1 mutant is defective for the expression of several genes, including genes involved in cell wall composition or modeling (Sawaki et al ., ). Furthermore, physiological studies suggested that stop1 seedlings are defective in a mechanism alleviating H + toxicity, perhaps via Ca 2+ stabilization of the cell wall (Kobayashi et al ., ). It is therefore tempting to speculate that even during WT embryogenesis STOP1 is participating in the making of root cells with a cell wall able to tolerate H + a few days after germination, and in stop1 seeds the root cell walls are somehow altered, leading to reduced root growth under acidic conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In Arabidopsis, Ca 2þ can reduce the concentration of Al 3þ in the plasma membrane to alleviate Al toxicity (Kobayashi et al, 2013). In wheat roots, the concentration of Al 3þ in plasma membrane of cells Fig.…”
Section: Sa and Ca 2þ Alleviate Al Toxicity In Soybeanmentioning
confidence: 99%
“…In most acidic soils, the major constraints of crop production include proton toxicity (low pH), Al 31 toxicity and cation deficiency (Muthukumar et al, 2014). Although proton toxicity differs from Al 31 toxicity in terms of mechanisms and symptoms (Kobayashi et al, 2013;Bose et al, 2015;Fan et al, 2015;Wehr et al, 2016), resistance to proton toxicity is regarded as the prerequisite for resistance to Al 31 toxicity (Rangel et al, 2005;Yang et al, 2005), highlighting the importance of proton toxicity resistance in adaptation to acidic soils. In addition to direct effects, low pH can reduce plant growth via indirect effects on nutrient availability, such as P. In acidic soils, soluble P is readily precipitated by Fe and Al or absorbed onto oxide surfaces, resulting in a low availability of P (Lee et al, 1990;Zhu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%